Bilateral primitive cholesteatoma of external auditory canal with congenital stenosis - Mahdoufi, R. (Int J Surg Case Rep, 2016)
• Primitive cholesteatoma of external auditory canal (EAC) is very rare and little known disease. • There are no specific clinical symptoms which can lead to confusion with other EAC pathologies. • Its diagnosis is clinical, but in case of stenosis, evaluation requires very close radiological analysis. • The treatment is surgical and depends on the extent of the lesions.